DAMPAK PELAKSANAAN FULL DAY SCHOOL TERHADAP DISIPLIN KERJA GURU - Utama, Hendri Budi; Al Kadri, Hanif; Kristiawan, Muhammad; Lian, Bukman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
The Government through the Minister of Education and Culture who is responsible for education issued Permendikbud number 23 of 2017 as a legal basis for full day school policy. Full day school has a negative impact on teachers. One of them has an impact on work discipline. With a variety of problems that occur in the field, ranging from lack of infrastructure to the behavior of students. The teacher will also experience the saturation point, coupled with the number of teacher assignments besides teaching such as administration of learning and so on. With the density of activities, many teachers carry out learning only as a routine, it happened because of the different theories with practice in implementing full day school.